Knowledge and decisions about maternal immunisation by pregnant women in Aotearoa New Zealand - Amber Young; Nadia A. Charania; Natalie Gauld; Pauline Norris; Nikki Turner; Esther Willing (BMC, 2022)
Abstract Background Maternal vaccinations for influenza and pertussis are recommended in New Zealand to protect mothers and their infant from infection. However, maternal immunisation coverage in New Zealand is suboptimal. Furthermore, there is unacceptable inequitable maternal immunisation rates across the country with Māori and Pacific women having significantly lower maternal immunisation rates than those of other New Zealanders. Methods This research set out to explore what pregnant/recently pregnant Māori and Pacific women knew about immunisation during pregnancy and what factors influenced their decision to be vaccinated. A semi-structured interview guide was developed with questions focusing on knowledge of pertussis and influenza vaccination during pregnancy and decision-making. Māori and Pacific women aged over 16 years were purposively sampled and interviewed in Dunedin and Gisborne, New Zealand between May and August 2021. Interviews were analysed following a directed qualitative content approach. Data were arranged into coding nodes based on the study aims (deductive analysis) informed by previous literature and within these participant experiences were inductively coded into themes and subthemes. Results Not all women were aware of maternal vaccine recommendations or they diseases they protected against. Many underestimated how dangerous influenza and pertussis could be and some were more concerned about potential harms of the vaccine. Furthermore, understanding potential harms of infection and protection provided by vaccination did not necessarily mean women would choose to be vaccinated. Those who decided to vaccinate felt well-informed, had vaccination recommended by their healthcare provider, and did so to protect their and their infant's health. Those who decided against vaccination were concerned about safety of the vaccines, lacked the information they needed, were not offered the vaccine, or did not consider vaccination a priority. Conclusions There is a lack of understanding about vaccine benefits and risks of vaccine-preventable diseases which can result in the reinforcement of negative influences such as the fear of side effects. Furthermore, if vaccine benefits are not understood, inaccessibility of vaccines and the precedence of other life priorities may prevent uptake. Being well-informed and supported to make positive decisions to vaccinate in pregnancy is likely to improve vaccine coverage in Māori and Pacific Island New Zealanders.